Examining Sigma and Beta convergence of economic growth in South Sulawesi, Indonesia - Fitrah Fitrah; Abd Rahman Razak; Sabir Sabir (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The purpose of this study is to determine the convergence of economic growth in the regencies and cities of South Sulawesi.Method — The type of data utilized in this study is quantitative, sourced from secondary data obtained from the Indonesian central statistics agency/ Badan Pusat Statistik of the districts and cities within South Sulawesi Province. The convergence analysis in this study is divided into two categories, namely sigma convergence and beta convergence. The application of sigma convergence aims to assess the level of disparity based on economic growth.Result — The results of the sigma convergence analysis indicate that there has been sigma convergence in South Sulawesi Province from 2015 to 2022, as evident from the decreasing Unweighted Coefficient of Variation value. Furthermore, the analysis of beta convergence was conducted using both absolute convergence and conditional convergence models, focusing on the economic growth of all districts/cities in South Sulawesi. The findings also reveal that the average length of schooling does not have a significant effect on economic growth. However, investment demonstrates a significant impact on the economic growth of districts/cities within the province of South Sulawesi.Contribution — The academic contribution of this study lies in its novel focus on convergence analysis of economic growth in regions/cities within South Sulawesi Province, specifically investigating the potential catching-up process and convergence in rising per capita income, which has been relatively overlooked in prior research predominantly centered on overall economic development at regional or national levels.